Pendidikan Karakter Keluarga Perspektif Tafsir Tarbawi: Studi Penafsiran Ali Abdul Halim Mahmud - Muhammad Rizqi Fauzan Adhimah; Fejrian Yazdajird Iwanebel (EduInovasi: Journal of Basic Educational Studies, 2025)
Character education is the provision given to an individual to shape their character or behavior, which needs to be implemented within the family. Family education is the inculcation of values or knowledge to the family, enveloped with religious teachings, thus creating a harmonious family through the cultivation of positive attitudes and behaviors derived from religious values developed within the family. The choice of this topic arises from the need for a deep understanding of Islamic teachings in the context of character education within the family. In the study of tafsir (Quranic exegesis), Ali Abdul Halim Mahmud has a work that interprets education, "Tafsir Tarbawi." This tafsir addresses educational issues, thereby supporting the development of civilization and knowledge related to the Quran. Therefore, this study will address Ali Abdul Halim Mahmud's views on the interpretation of verses regarding family education in Tafsir Tarbawi and its implications for family character education. This research employs a qualitative model and uses a descriptive approach with a thematic tafsir research type. The results of the study indicate that Ali Abdul Halim Mahmud's views on family character education highlight key concepts such as faith, morality, and the role of parents. These findings are supported by his interpretation of specific verses that emphasize the importance of Islamic values in shaping character. He underscores the importance of maintaining self-purity, covering the aurat (parts of the body that should be covered), and avoiding actions that can lead to slander. This provides a general perspective on character education within religious values and social ethics. Thus, this research can be used as a guideline in developing a more effective family character education program, in line with Islamic teachings.